The electrification of underdeveloped areas : a case study in Ciskei - Tobich, Ralf Georg (Department of Electrical Engineering, 2016)
More than 20 million people in South Africa live without electricity in the household. Perhaps half of them live in underdeveloped rural areas in the 'homelands', which comprise about 14% of South Africa's land area. While considerable work has been done on methods of electrifying underdeveloped urban areas, little research has gone into the need for, and especially the cost of, electrifying the rural homeland areas. This dissertation documents an investigation into this question, using Ciskei as a sample area. The study is based on research that was carried out between July 1987 and January 1989. This research included a literature review of rural electrification and development, two field trips to Ciskei to gather relevant information, two questionnaire surveys to assess people's perceptions of electricity, and the design and costing of distribution and reticulation networks for a rural sample area in Ciskei.